Comparative evaluation of naftopidil and tamsulosin in the treatment of patients with lower urinary tract symptoms with benign prostatic hyperplasia - Mahavir Singh Griwan; Y. R. Karthikeyan; Mandeep Kumar; Bikram Jit Singh; Santosh Kumar Singh (Urology Annals, 2014)
Introduction: Naftopidil, approved initially in Japan, is an α1d-adrenergic receptor antagonist (α1-blocker) used to treat lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). It is different from tamsulosin hydrochloride and silodosin, in that it has a higher affinity for the α1D-adrenergic receptor subtype than for the α1A subtype and has a superior efficacy to a placebo and comparable efficacy to other α1-blockers such as tamsulosin. The incidences of ejaculatory disorders and intraoperative floppy iris syndrome induced by naftopidil may also be lower than that for tamsulosin and silodosin, which have a high affinity for the α1A-adrenergic receptor subtype. However, it remains unknown if the efficacy and safety of naftopidil in Japanese men is applicable to Indian men having LUTS/BPH. Material and Methods: Two groups of 60 patients each, having LUTS due to BPH, were treated with tamsulosin 0.4 mg and Naftopidil 75 mg for three months. Ultrasonography (for prostate size, post-void residual volume), uroflowmetry, and the International Prostate Symptom Score (IPSS) and Quality of Life (QOL) score were recorded at the beginning of the study, and then at one and three months. Results: The prostate size, post-void residual volume, all the uroflowmetry variables, and the IPSS QOL scores showed a statistically significant improvement (P < 0.001) in both the groups. The improvement in the average flow rate and the QOL index was better in the naftopidil group on the intergroup comparison and was statistically significant (P < 0.001). C onclusion: Although the QOL life index was significantly better in the naftopidil group, overall both naftopidil and tamsulosin were found to be equally effective in the treatment of LUTS due to BPH.